Bisphenol A mediated histopathological, hemato-biochemical and oxidative stress in rabbits (Oryctolagus cuniculus). (2nd October 2022) - Afzal, Gulnaz; Ahmad, Hafiz Ishfaq; Jamal, Adil; Mustafa, Ghulam; Kiran, Shumaila; Hussain, Riaz; Anjum, Shazia; Rafay, Muhammad; Ghaffar, Abdul; Saeed, Saba
Abstract: Bisphenol A (BPA) is a ubiquitous environmental contaminant and is commonly known as an endocrine disrupting chemical (EDC). BPA is widely used in production of numerous products including polycarbonate plastics, cans, drinking water bottles and dental sealants. Therefore, the current study was designed to investigate deleterious effects of BPA on blood, serum biochemistry, antioxidant enzymes and histopathological changes in different visceral organs of exposed rabbits. For this reason a total of 16 male rabbits were randomly divided and kept in four different groups (A-D). Rabbits in control group A received no treatment and were kept on normal feed while the rabbits in groups B, C and D were administered BPA @ 10, 50 and 100 mg/kg/day respectively by oral gavage for 28 days. The results showed significant decrease in hemoglobin level, total proteins, lymphocytes, packed cell volume (PCV), red blood cells (RBC) and monocytes in treated rabbits compared to control group. The total white blood cell count and neutrophil (%) significantly increased in treated rabbits. The serum biochemistry analysis showed that the concentrations of glucose, cholesterol, triglycerides, high density lipoprotein (HDL) and low density lipoprotein (LDL) were significantly (p<0.05) higher in the treated rabbits. Results revealed that the levels of various antioxidant enzymes such as peroxidase (POD), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) were significantly decreased (p<0.05) in rabbits exposed to BPA. The quantity of oxidative stress biomarker such as malondialdehyde (MDA) significantly increased in all treated animals compared to control group. Microscopic observation of different visceral tissues like liver, kidneys, lungs and heart exhibited necrotic and degenerative lesions in treated rabbits. In conclusion, the results of our experimental study suggested that BPA induces hemato-biochemical, histopathological and oxidative stress in male rabbits.